Analisis Bibliometrik Penelitian tentang Gangguan Tidur Pada Pasien Stroke - Hety Meiliany; Azizah Khoiriyati (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Sleep disorders are a risk factor for complications frequently experienced by stroke patients. Research on sleep and stroke continues to increase, but few studies have comprehensively mapped scientific developments in this field. This study aims to analyze global research trends, distribution, and themes related to sleep disorders in stroke patients through a bibliometric approach. This research method uses a quantitative bibliometric approach. Data were obtained from the Scopus database with a period of 2010-2025 using the keywords "sleep wake disorder" AND "stroke" with subject filters of medicine, neurology, nursing, and health. Analysis was conducted on 225 English-language articles that met the inclusion criteria. Data processing was carried out using VOSviewer software to display keyword network visualizations, temporal trends, and country collaboration maps. The results obtained are the number of publications increased significantly since 2010 and peaked in 2025 with 39 articles. The United States was the country with the most publications (69 articles). Keyword analysis revealed three main clusters of research on sleep disorders and post-stroke rehabilitation: physiological mechanisms, including sleep apnea and brain ischemia; and third, cardiovascular comorbidities such as hypertension and sleep duration. The most frequently occurring keywords are sleep disorders, stroke, cerebrovascular accident, and sleep apnea syndromes. Research on sleep disorders in stroke patients shows a rapid increase and a shift in focus from descriptive studies to clinical and physiological approaches. Keywords: Bibliometrics, Sleep Disorders, Stroke.  ABSTRAK Gangguan tidur merupakan faktor risiko komplikasi yang sering dialami oleh pasien stroke. Penelitian mengenai tidur dan stroke terus meningkat, belum banyak kajian yang memetakan perkembangan ilmiah di bidang ini secara komprehensif. Adapun  Penelitian ini bertujuan untuk menganalisis tren, sebaran, dan tema penelitian global terkait gangguan tidur pada pasien stroke melalui pendekatan bibliometrik. Metode Penelitian ini menggunakan pendekatan bibliometrik kuantitatif. Data diperoleh dari basis data Scopus dengan batasan tahun 2010-2025 menggunakan kata kunci “sleep wake disorder” AND “stroke” dengan filter subjek medicine, neurology, nursing, dan health. Analisis dilakukan terhadap 225 artikel berbahasa Inggris yang memenuhi kriteria inklusi. Pemrosesan data dilakukan menggunakan perangkat lunak VOSviewer untuk menampilkan visualisasi jejaring kata kunci, tren temporal, serta peta kolaborasi negara. Hasil yang didapatkan yaitu jumlah publikasi meningkat secara signifikan sejak 2010 dan mencapai puncak pada 2025 dengan 39 artikel. Amerika Serikat menjadi negara dengan publikasi terbanyak (69 artikel). Analisis kata kunci menunjukkan tiga kluster utama penelitian gangguan tidur dan rehabilitasi pasca-stroke; yang kedua mekanisme fisiologis, termasuk sleep apnea dan brain ischemia; serta yang ke 3 komorbiditas kardiovaskular seperti hipertensi dan durasi tidur. Kata kunci yang paling sering muncul adalah sleep disorder, stroke, cerebrovascular accident, dan sleep apnea syndromes. Penelitian mengenai gangguan tidur pada pasien stroke menunjukkan peningkatan yang pesat dan pergeseran fokus dari kajian deskriptif menuju pendekatan klinis dan fisiologis. Kata Kunci: Bibliometrik, Gangguan Tidur, Stroke.